HUBUNGAN TGF-β1 DAN ESTROGEN DENGAN VOLUME PROSTAT PADA PASIEN BPH, PASIEN TUA NON BPH, DAN PASIEN MUDA - Soebhali, Boyke; Soetojo, Soetojo; Soebadi, Doddy M; Hendromartono, Hendromartono; P, Widodo J (Indonesian Urological Association, 2009)
Objective: To determine the correlation of TGF-b1 and estrogen with prostate volume in BPH patients, old patients without BPH and young patients. Materials and methods: We enrolled 30 patients and allocated them into three groups. First group consists of BPH patients, second group consists of old male patients with more than 55 years of age, and third group consists of young male patients with less than 40 years of age. We analyzed the level of TGF-b1 and estrogen in these patients. Transrectal USG was used to measure the prostate volume. We analyzed the correlations of TGF-b1 and estrogen level with prostate volume. Results: We found a positive strong correlation between estrogen and prostate volume in the BPH patient group (p=0,021; r coeff=0,786). Other group showed no significant correlations. Conclusion: Estrogen plays an important role in BPH pathophysiology. Further research on the influence of estrogen in BPH patients is recommended.